Pemilihan Auditor Internal dalam Mengimplementasikan Pendekatan Metode Multi Attribute Utility Theory (MAUT) dan Menerapkan Pembobotan Rank Order Centroid (ROC) - Mohammad Aldinugroho Abdullah; Rima Tamara Aldisa (Jurnal Sistem Komputer dan Informatika (JSON), 2023)
The Internal Auditor of a company is a professional responsible for evaluating, overseeing, and providing independent assessments of the effectiveness of internal controls, accounting systems, and business processes of a company. The primary task of the internal auditor is to assist the company's management in ensuring that its operations adhere to applicable standards, policies, and regulations. The presence of an internal auditor helps the company maintain integrity, accountability, and compliance with relevant standards and regulations. They provide an independent view of the company's performance and aid in enhancing operational efficiency and effectiveness. In the complex business world, selecting a candidate for the role of Internal Auditor poses a challenge. Diverse selection criteria, such as auditing skills, industry knowledge, and integrity, often prove difficult to objectively assess. Decision-making based solely on experience can lead to inconsistent outcomes. The importance of accuracy and objectivity in selecting an Internal Auditor demands a scientific approach. The Multi-Attribute Utility Theory (MAUT) analysis method is employed to address the complexity of criteria. Meanwhile, the Rank Order Centroid (ROC) method is used to assign weights to each criterion. By combining MAUT and ROC in a support system, companies have a more structured and measurable way to select potential Internal Auditors. This approach is expected to help overcome issues in candidate selection that often do not align with the company's needs, and to provide more accurate and objective decisions. The ultimate result obtained by applying the MAUT method is a value of 0.794, which is the highest ranking among the 7 selected alternatives. The highest ranking result associated the seventh alternative, named Poppy Rosana.